2022
DOI: 10.1021/acsomega.2c01562
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Enhancing Catalytic Performance and Increasing Density of Bifunctional CuN3 Active Sites in Dopant-Free 2D C3N3Cu for Oxygen Reduction/Evolution Reactions

Abstract: Atomically dispersed M–N–C has been considered an effective catalyst for various electrochemical reactions such as oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), which faces the challenge of increasing metal load while simultaneously maintaining catalytic performance. Herein, we put forward a strategy for boosting catalytic performances of a single Cu atom coordinated with three N atoms (CuN 3 ) for both ORR and OER by increasing the density of connected CuN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…The effects of inter-site distance and surface curvature on electrocatalytic activity have been discovered recently. [21][22][23] On the one hand, the previously reported surface curvature effect mimics the well-known strain effect. 24 On the other hand, to the best of our knowledge, the surface curvature effect that enhances dual-atom site catalysis remains unknown.…”
supporting
confidence: 58%
“…The effects of inter-site distance and surface curvature on electrocatalytic activity have been discovered recently. [21][22][23] On the one hand, the previously reported surface curvature effect mimics the well-known strain effect. 24 On the other hand, to the best of our knowledge, the surface curvature effect that enhances dual-atom site catalysis remains unknown.…”
supporting
confidence: 58%
“…24,25 Other literature studies also suggested that the CuN 3 moiety promotes the formation of reactive intermediates such as Cu–oxo species. 26–28…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Other literature studies also suggested that the CuN 3 moiety promotes the formation of reactive intermediates such as Cu-oxo species. [26][27][28] Under the optimized reaction conditions, the reusability of the CuNC catalyst was assessed (Fig. S12 †).…”
Section: Catalytic Activity Of Cunc Catalystsmentioning
confidence: 99%
“…The general effects of intersite distance and surface curvature on electrocatalytic activity have been discovered just recently. On the one hand, the previously reported surface curvature effect mimics the well-known strain effect . On the other hand, to the best of our knowledge, the surface curvature effect that enhances dual-atom site catalysis and goes beyond the scaling relations remains unknown.…”
mentioning
confidence: 89%